Effects of Annealing Conditions on the Catalytic Performance of Anodized Tin Oxide for Electrochemical Carbon Dioxide Reduction - Nicolò B. D. Monti; Juqin Zeng; Micaela Castellino; Samuele Porro; Mitra Bagheri; Candido F. Pirri; Angelica Chiodoni; Katarzyna Bejtka (Nanomaterials)
The electrochemical reduction of CO2 (CO2RR) to value-added products has garnered significant interest as a sustainable solution to mitigate CO2 emissions and harness renewable energy sources. Among CO2RR products, formic acid/formate (HCOOH/HCOO−) is particularly attractive due to its industrial relevance, high energy density, and potential candidate as a liquid hydrogen carrier. This study investigates the influence of the initial oxidation state of tin on CO2RR performance using nanostructured SnOx catalysts. A simple, quick, scalable, and cost-effective synthesis strategy was employed to fabricate SnOx catalysts with controlled oxidation states while maintaining consistent morphology and particle size. The catalysts were characterized using SEM, TEM, XRD, Raman, and XPS to correlate structure and surface properties with catalytic performance. Electrochemical measurements revealed that SnOx catalysts annealed in air at 525 °C exhibited the highest formate selectivity and current density, attributed to the optimized oxidation state and the presence of oxygen vacancies. Flow cell tests further demonstrated enhanced performance under practical conditions, achieving stable formate production with high faradaic efficiency over prolonged operation. These findings highlight the critical role of tin oxidation states and surface defects in tuning CO2RR performance, offering valuable insights for the design of efficient catalysts for CO2 electroreduction to formate.